1990
DOI: 10.2118/15648-pa
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Oxidation of Viscous Crude Oils

Abstract: Summary. During in-situ combustion, oxygen can bypass the flame front and react with oil temperatures that are relatively low compared with those in combustion. These reactions, called low-temperature oxidation (LTO), can adversely affect the crude's physical and chemical properties and result in lower oil recovery. This paper presents laboratory study results on the LTO of four oils, ranging from 31.1 to 10.1deg. API and from 14 to 54,300 cp dead-oil viscosity at 85deg.F. They include two bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 13 publications
1
48
0
1
Order By: Relevance
“…Fassihi et al showed that LTO did not change the distribution of carbon number in light or heavy oils [5]. This implies that elemental ratios between carbon and hydrogen, carbon and oxygen, and hydrogen and oxygen can describe the conversion of bonds in oil molecules to the major functional groups of products of the LTO reactions.…”
Section: Elemental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fassihi et al showed that LTO did not change the distribution of carbon number in light or heavy oils [5]. This implies that elemental ratios between carbon and hydrogen, carbon and oxygen, and hydrogen and oxygen can describe the conversion of bonds in oil molecules to the major functional groups of products of the LTO reactions.…”
Section: Elemental Analysismentioning
confidence: 99%
“…According to their results, LTO had no significant effect on light oil samples, but led to dramatic changes in heavy oil properties. For example, they showed that the viscosity of a heavy oil sample from Monterey that had undergone LTO was raised from 54,300 cP at 85°F to 791,151 cP at 350°F [4,5]. Freitag and Verkoczy investigated LTO of the SARA (saturate, aromatic, resin and ashphaltene) fractions of two different oil samples mixed with reservoir sand and found that the order of reaction with respect to the oxygen concentration varied from half to one, as the temperature was raised.…”
Section: Introductionmentioning
confidence: 99%
“…Contrastive studies of the displacement efficiency between water and gas displacement have undertaken in the N block of L oilfield in the Bohai Bay basin [18][19][20][21][22]. The block has been exposed to water flooding, thus two types of experiments were performed: direct water flooding and gas driving after water flooding, in order to get in line with the actual situation.…”
Section: Oil Displacement Experimentsmentioning
confidence: 99%
“…In situ combustion (Belgrave et al, 1990;Belgrave and Moore, 1992;Moore et al, 1999a,b) and high pressure air injection (Fassihi et al, 1990;Moore et al, 2002;Ren et al, 2002;Shokoya et al, 2004) are thermal enhanced oil recovery techniques for which oxidation of oils is of special importance. In addition to the main concern of stabilizing a burning front, in these processes, it is of vital importance to know the impacts of the oxidation on the rheological properties of the oil.…”
Section: Introductionmentioning
confidence: 99%